Contribution of long noncoding RNA HOTAIR variants to preeclampsia susceptibility in Iranian women. (2nd January 2021) - Esmkhani, Sahra; Sadeghi, Hossein; Ghasemian, Majid; Pirjani, Reihaneh; Amin-Beidokhti, Mona; Gholami, Milad; Yassaee, Fakhrolmolouk; Mirfakhraie, Reza
ABSTRACT: Objective : To investigate the possible association of lncRNA HOTAIR rs920778 and rs874945 polymorphisms with preeclampsia risk in a sample from the Iranian population. Method : The study subjects included 250 preeclamptic women and 250 healthy women. The genotyping for rs920778 and rs874945 polymorphisms were performed using the TP-ARMS-PCR method. Results : HOTAIR rs920778 increased the risk of preeclampsia under the dominant and recessive inheritance patterns (OR = 4.84, 95% CI: 3.30–7.10, P < 0.0001; OR = 6.86, 95% CI: 3.51–13.42, P < 0.0001; respectively). Conclusion : This study confirmed the association of HOTAIR rs920778 polymorphism with preeclampsia in Iranian women. Further studies should be performed to confirm our findings.